1984
DOI: 10.1007/bf00205745
|View full text |Cite
|
Sign up to set email alerts
|

The in situ activation of cytotoxic properties in murine Kupffer cells by the systemic administration of whole Mycobacterium bovis organisms or muramyl tripeptide

Abstract: We determined whether the systemic administration of viable Mycobacterium bovis organisms (BCG) or a lipophilic derivative of muramyl tripeptide (MTP-PE) would lead to the activation of antitumor properties in murine Kupffer cells (KC). KC-mediated tumor cytolysis was determined by the release of radiolabeled nuclear breakdown products of target cells. KC harvested from either C57BL/6 or C3H/HEN mice treated with saline exhibited no cytotoxicity against syngeneic B16 melanoma or UV-2237 fibrosarcoma cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…4 and 5). Precedent for BRM-mediated augmentation of organ-associated macrophage-mediated cytocidal activity comes from previous studies which have shown that liposome-encapsulated immunomoduoators activate alveolar macrophages [8,10,12,33] and Kupffer cells [50], and mediate antimetastatic effects [7,9,10]. Based on these previous observations, coupled with our studies showing augmentation of liver-associated NK activity by P. aenes (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…4 and 5). Precedent for BRM-mediated augmentation of organ-associated macrophage-mediated cytocidal activity comes from previous studies which have shown that liposome-encapsulated immunomoduoators activate alveolar macrophages [8,10,12,33] and Kupffer cells [50], and mediate antimetastatic effects [7,9,10]. Based on these previous observations, coupled with our studies showing augmentation of liver-associated NK activity by P. aenes (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, other studies have reported liver-derived NK activity to be associated with cells having large granular lymphocyte (LGL)-like morphology [23,28,47]. Recently, Xu and Fidler [50] demonstrated that Kupffer cells isolated from mice pretreated with either Mycobaeterium bovis or MTP-PE were cytotoxic for B16 melanoma or UV-2237 fibrosarcoma tumor cells. The present study was designed to determine whether BRMs could augment the cytolytic activity of both liverassociated NK cells and Kupffer cells, and further to demonstrate whether tumoricidal activity mediated by cytolytic macrophages could be distinguished from NK activity.…”
Section: Discussionmentioning
confidence: 95%
“…The systemic administration of muramyl tripeptide and whole Mycobacterium bovis organisms in vivo significantly stimulated KC cytotoxicity in vitro against UV 2237 fibrosarcoma and B16 melanoma target cells [25]. Further, the in vivo administration of LPS stimulated three-fold the in vitro KC killing of rat NIS1 hepatoma and RBL-1 basophilic leukemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…The recent finding that liposome-encapsulated MTP-PE also activates human blood monocytes to become tumouricidal is an importam step towards the development of this compound for its applicability as a possible "anti-cancer drug" [13,23]. Also, if MTP-PE dissolved in buffer is injected into mice i.v., tumouricidal macrophages (Kupffer cells) are induced [24]. Furthermore, MTP-PE solubilized in buffer exerts prophylactic and therapeutic anti-viral effects after single intranasal, p.o.…”
Section: Introductionmentioning
confidence: 99%